Potensi Industri Kecil Di Desa Wombo Kalonggo Kecamatan Tanantovea Kabupaten Donggala - Rahma, Siti; Budianta, Aziz (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2024)
The small industry is a form of the people's economy that has the potential to develop the people's economy and have an impact on increasing the national economy and can help overcome the problem of unemployment. In 2020 the economy of Donggala Regency experienced a decline which reached -4.26 percent but in 2021 again showed positive growth reaching 4.64 percent. Wombo Kalonggo Village has several small industries that have the potential to be developed, including the fried onion and copra industries. The types of data used in this study are primary data and secondary data. The data analysis technique used in this research is descriptive analysis.The results of this study indicate that there are two small industries in Wombo Kalonggo Village, namely fried onion production and copra production. The business potential for fried onions and copra in Wombo Kalonggo Village is still very large. This is supported by the geographical location and the potential of local commodities in the development of fried onion and copra industries. The development of the fried onion and copra business is so rapid as evidenced by the fact that the marketing already exists outside the city of Palu and there are even buyers who come directly to the production site. An increase or decrease in sales depends on market prices and the needs of consumers who consume fried onions, while for copra the increase or decrease in sales depends on product quality and weather conditions. Constraints are faced by the lack of capital and raw materials.